Diversity and distribution of the superfamily Grylloidea (Orthoptera: Ensifera: Gryllidea) in the Nearctic region - Zhao, Xin; Feng, Dandan; Li, Yuntao; Liu, Haoyu (Zootaxa, 2021)
Based on the geographic distribution database of the Orthoptera Species File, the diversity and distribution of the superfamily Grylloidea in the Nearctic region was studied using the statistics and Sorensen dissimilarity coefficient. A total of 164 species or subspecies belonging to 4 families, 9 subfamilies and 27 genera were recorded from this region; among which Gryllidae (93, 56.70%), followed by Trigonidiidae (44, 26.83%), Mogoplistidae (25, 15.24%), and Phalangopsidae (2, 1.22%). The diversity exhibits an asymmetric distribution pattern, with the southeastern coastal plain, the Interior Plateau and Piedmont of the United States was the most abundant. At the same time, the regional similarity of species distribution was analyzed, and the Nearctic was divided into four subregions: Boreal & Arctic zone of North America, Eastern temperate North America, Northeast temperate North America, and Southern North America & western temperate North America.